Plato's ideas in Lotze's light: on Husserl's reading of Lotze's Logik - Arnold, Thomas (Husserl studies, 2023)
Recent scholarship has shed more light on the relationship between Husserl and Lotze. And Husserl indeed claims of Lotze that “his inspired interpretation of the Platonic doctrine of Forms […] put up a bright first light and determined all further studies” (2002a, 297). In this paper I will try to answer the question what exactly Husserl saw in this “bright light”—the answer being much more complicated than “Platonism.” As I will show, Lotze misreads Plato, but in interesting ways, and Husserl in turn misreads Lotze. In other words, this paper is about a misreading of a misreading—yet one fundamental for the development of phenomenology in that Husserl’s engagement with Lotze enabled him (a) to expand and differentiate his own anti-reductionism in regard to ideal entities, leading him to two forms of what he calls “Platonism,” one of which even runs contrary to Lotze’s own account, and (b) to conceive of a method to gain truths about the material apriori. After a brief introduction, I will discuss (1) Lotze’s interpretation of Plato, (2) what Husserl took from it, and finally (3) Plato’s Platonism, to substantiate my claims1.
Online veröffentlicht: 17. Dezember 2022
Gesehen am 28.08.2024